Landslide Susceptibility Assessment Using the Integration of Frequency Ratio and Weight of Evidence Model in North Luwu, South Sulawesi, Indonesia - Azikin, Busthan; Pachri , Hendra; Alimuddin , Ilham; Eden , Johan (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The Masamba area of North Luwu Regency has been hit by a flash flood disaster on July 13, 2020. The flash flood claimed dozens of lives, hundreds of people were injured and thousands of houses were submerged. Based on the analysis of several information, the cause of the flash flood in Masamba was due to high rainfall and landslides that occurred in the upstream area. Land movement vulnerability zoning is needed in this area to provide information in making disaster mitigation policies for post-disaster planning and development. Frequency Ratio and Weight of Evidence methods were applied in this study by using parameters such as: slope, lithology, land cover, rainfall, slope direction, slope convexity, distance from river, distance from fault and soil type. The Weight of Evidence method provides more accurate results with an accuracy rate of 99.83%. Vulnerability zoning of landslides in the Masamba area are grouped into 5 classes; The zone of vulnerability to soil movement is very high, around 6,822.27 ha or about 25.47% of the research area. The high ground movement vulnerability zone is about 4261.84 ha or about 15.91% of the research area.